Peningkatan Kepatuhan Hukum Dan Akses Pendanaan UMKM Melalui Penyuluhan Legalitas Usaha - Fathurrohman; Indra Wiguna Marthanu; Rheznandya Fahreza; Tubagus Muhammad Rayhan (AMMA : Jurnal Pengabdian Masyarakat, 2024)
This Community Service (PKM) activity aims to provide outreach regarding business legality for Micro, Small, and Medium Enterprises (UMKM) in the Xxxx area. The main problem identified is the low level of legal compliance among UMKM concerning business permits, which impacts limited access to formal funding and business development. This activity was carried out by the proposing team from STMIK IKMI Cirebon on July 3, 2024. The PKM implementation methods included socialization, presentation of outreach materials, interactive discussions, and assistance with business permit processing. The results of this activity are expected to increase the understanding and awareness of UMKM actors regarding the importance of business legality, encourage compliance with statutory regulations, and open up broader access to funding sources and UMKM development programs. Furthermore, this activity is also expected to make a positive contribution to local economic growth through the empowerment of legal and competitive UMKM.